Women's community participation and management of public policies in a popular neighborhood in Rosario (Argentina) - González, Gabriela (2018)
In this work we propose to analyze the trajectory of an organization formed by women from a peripheral neighborhood of Rosario?s city (Argentina). From an ethnographic approach we try to account for how in the way of organizing and managing resources, there is a passage from the private to the public, leading family concerns (children stalked by drugs, violence, poverty) and domestic activities (cooking , clean, take care of children) to the community sphere. In this way, the political practices of these women, which are linked to the collective participation from a particular woman-mother role, do not become exceptional biographies? We suggest that these political practices appear in the daily life, in personal relationships, among friends, neighbors, relatives and in links with state and social institutions.